2023
DOI: 10.3390/antiox12020269
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Gallate Isolated from Castanopsis cuspidata var. sieboldii Branches Inhibits Melanogenesis and Promotes Autophagy in B16F10 Cells

Abstract: The Castanopsis cuspidata var. sieboldii (CCS) plant grows predominantly in temperate regions of Asian countries, such as South Korea. Research on CCS has so far concentrated on the nutritional analysis, antioxidant activity, and anti-inflammation properties of its branches. However, the isolation of compounds and structural elucidation of effective single molecules remain unexplored, necessitating further exploration of CCS branches. Therefore, this study demonstrates the antioxidant and antimelanogenic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Ascorbic acid, used as a positive control, exhibited an IC 50 of 36.61 ± 1.92 μg/mL in the DPPH assay and 37.37 ± 2.11 μg/mL in the ABTS assay. In addition, we recently identified the antioxidant capacity of five fractions of CSL3 (n-hexane, chloroform, ethyl acetate, n-butanol, and water) and isolated polyphenolic compounds [ 24 ]. Experimental results revealed that EtOAc fractions of CSL3 had the highest radical scavenging activity and contained total polyphenol contents (TPC) and total flavonoid contents (TFC).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ascorbic acid, used as a positive control, exhibited an IC 50 of 36.61 ± 1.92 μg/mL in the DPPH assay and 37.37 ± 2.11 μg/mL in the ABTS assay. In addition, we recently identified the antioxidant capacity of five fractions of CSL3 (n-hexane, chloroform, ethyl acetate, n-butanol, and water) and isolated polyphenolic compounds [ 24 ]. Experimental results revealed that EtOAc fractions of CSL3 had the highest radical scavenging activity and contained total polyphenol contents (TPC) and total flavonoid contents (TFC).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, CSL3 had the highest content of polyphenols with 4264.20 ug/g, followed by CSL1, CSL2, and CSL4 ( Figure S1 ). In our previous study, the components detected in the EtOAc fraction of the CS were high in the order of ethyl gallate, gallic acid, and chlorogenic acid [ 24 ]. However, the content of EGCG was the highest, and gallic acid, protocatechuic acid, and chlorogenic acid were mainly detected in the current study.…”
Section: Resultsmentioning
confidence: 99%